Aplicativo móvil de música en idioma huitoto y su relación con la identidad cultural de los pobladores en el centro arenal, 2020 - Vásquez Ocmin, Adrián (2021)
The purpose of this research project is: To develop and implement a mobile application of music in the Huitoto language in order to determine the association with the cultural identity of the inhabitants of Centro Arenal and for its development we took into account the quantitative approach, with a level relational, supported by a data collection methodology, whose research design was non-experimental of a transactional type, the study population that is made up of residents of the Centro Arenal village, whose sample was 25 inhabitants of legal age, the sampling was for convenience. The technique used to collect data from the independent variable, mobile application of songbook in the Huitoto language, and the dependent variable, cultural identity of the inhabitants is the structured survey and the instrument a questionnaire, after analyzing the results and with the In an effort to provide answers to the proposed objectives, the following conclusions were reached: 60% of the inhabitants of Centro Arenal feel very satisfied with the implementation of a mobile application of music in the Huitoto language, 60% of the inhabitants of Centro Arenal if they identify with their culture and there is a significant relationship between the implementation of a mobile application of music in the Huitoto language and the cultural identity of the inhabitants of Centro Arenal.